ANALISIS TRANSMISI AIR SISTEM PENGANGKATAN AIR TENAGA SURYA DI GUA PLAWAN, DESA GIRICAHYO, KECAMATAN PURWOSARI, GUNUNG KIDUL, DI YOGYAKARTA - , YOGA ISMAIL RAMBUGASI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Giricahyo village is karst area where water shortages is common in every year. In 2010 there was damage to the Solar Water Pumping System (SWPS) already installed. The pump was broken in the mechanical parts. The system worked by 2-time lifting. This study aims to determine the characteristics of the pipeline network in order to choose the appropriate pump with a power capacity of 1.2 kWp, and then calculate the capacity of water that can be lifted. The research was conducted by studying literature and doing field survey to find out the population of the village Giricahyo, the data of piping system had been installed, and pump specifications. Pump PS1200 PS1200 HR-07 and HR-04H were chosen for the system. At the first lifting, it is used Configuration 3 by using 5 Pump PS1200 HR-07, and Configuration 2 by using 4 Pump PS1200 HR-07 and 1 PS1200 04H at the second lifting. Based on the power scenario that was created, the system is able to meet the basic water needs for 22.4% of the people. In actual field conditions, the solar panels output energy utilized by the pump to produce a flow may change due to the changing value of the inverter efficiency. The efficiency of the inverter changes depend on the value of the output of solar panels as an input inverter.